Hubungan Antara Tingkat Religiusitas Orang Tua dengan Religiusitas Siswa - Alfin Maskur (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
Children are individuals who determine the future and quality of the nation, so it is important to consider the development of the child, namely physical development, psychiatric and spirituality. A strong base of planting through the guidance and religious education, the role of family began to weaken because of the social, political and cultural changes that occurred. The family has lost its function in student emotion development especially in the adolescent phase. The purpose of this research is to test the relationship of parents ' religiality to the level of religiality of students of XI MAN Prambon class. Using the quantitative approach of the results of this research is as follows: (1) The level of religiality of parents of class XI MAN Prambon is categorized as excellent based on the mean value of 130, 718 which is guided by the absolute score criteria ; (2) The level of religiality of students of the class XI MAN Prambon is categorized very well based on the mean value of 127,971 which is guided by the absolute score criteria; (3) There is a significant relationship with the level of parents ' religiality and the level of religiality of class students of XI MAN Prambon with the correlation value of product moment of 0765 that is greater than the value of R table and the value of Sig under 0.05 is 0.000.